2006
DOI: 10.21273/hortsci.41.3.768
|View full text |Cite
|
Sign up to set email alerts
|

Tomato Early Seedling Height Control Using a Paclobutrazol Seed Soak

Abstract: Tomato seedling hypocotyls elongate rapidly after germination resulting in weak seedlings. The effects of 0, 250, 500, 750, or 1000 mg paclobutrazol (PB)/L seed soak and soaking times from 1 to 12 hours on tomato (Solanum lycopersicum L.) seed germination, seedling growth, and plant growth were tested. Adequate height control was obtained with 250 mg PB/L while soaking time did not affect seedling growth. In a second experiment, PB was tested at 0, 50, 100, 150, 200, or 250 m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 15 publications
0
5
0
Order By: Relevance
“…Early seedling establishment is crucial for survival in many crops. For example, tomato plants with long hypocotyls are quite fragile, which can lead to the loss of many seedlings during mechanical planting (Brigard et al, 2006). Conversely, early elongation may aid competition against weeds.…”
Section: Chimeric Arabidopsis Hy5 Can Modulate Growth In Tomatomentioning
confidence: 99%
“…Early seedling establishment is crucial for survival in many crops. For example, tomato plants with long hypocotyls are quite fragile, which can lead to the loss of many seedlings during mechanical planting (Brigard et al, 2006). Conversely, early elongation may aid competition against weeds.…”
Section: Chimeric Arabidopsis Hy5 Can Modulate Growth In Tomatomentioning
confidence: 99%
“…As a result of the literature review, investigates the effects of the application of tebuconazole to tomatoes and other vegetable species on their seedling quality was limited studies [Mohsin et al 2019, Bulut et al 2021. However, several studies investigating the effects of paclobutrazol and similar substances, which are included in triazol group similarly with tebuconazole, on vegetable seedling quality are available [Brigard et al 2006, Çopur and Sarı 2012, Geboloğlu et al 2015, Uçan 2019. Geboloğlu et al [2015] applied four different doses of paclobutrazole (50, 100, 200 and 500 ppm, respectively) to eggplant seedlings in 2 different seedling development stages and found that seedling height and stem height were significantly suppressed as a result of this application.…”
Section: Discussionmentioning
confidence: 99%
“…There are studies investigating the effects of Paclobutrazol and similar substances, which belong to the Triazole group similar to tebuconazole, on vegetable seedling characteristics and quality (Brigard et al, 2006;Çopur and Sarı, 2011;Geboloğlu et al, 2015;Geboloğlu et al, 2016;Uçan, 2019). In a study conducted on eggplant, the tebuconazole applied at different doses significantly decreased the seedling length and stem length (Öztürk and Dursun, 2020).…”
Section: Discussionmentioning
confidence: 99%